War Time - Halewood, Louis. (Milton)
1 online resource (235 p.)
Keywords: The International Society for First World War Studies' ninth conference, 'War Time', drew together emerging and leading scholars to discuss, reflect upon, and consider the ways that time has been conceptualised both during the war itself and in subsequent scholarship. War Time: First World War Perspectives on Temporality, stemming from this 2016 conference, offers its readers a collection of the conference's most inspiring and thought-provoking papers from the next generation of First World War scholars. In its varied yet thematically-related chapters, the book aims to examine new chronologies of the Great War and bring together its military and social history. Its cohesive theme creates opportunities to find common ground and connections between these sub-disciplines of history, and prompts students and academics alike to seriously consider time as alternately a unifying, divisive, and ultimately shaping force in the conflict and its historiography.?With content spanning land and air, the home and fighting fronts, multiple nations, and stretching to both pre-1914 and post-1918, these ten chapters by emerging researchers (plus an introductory chapter by the conference organisers, and a foreword by John Horne) offer an irreplaceable and invaluable snapshot of how the next generation of First World War scholars from eight countries were innovatively conceptualising the conflict and its legacy at the midpoint of its centenary.?.